HUMAN RESOURCES EXPERIENCES IN HYBRID WORKING MODELS: A QUALITATIVE STUDY OF THE IMPACT ON BEHAVIOUR AND PERFORMANCE - Kurniawan, Zuki; Hamamah, Fatin; Erna, Erna; Sukama, Sukama; Eliyawati, Eliyawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Hybrid working models have become an increasing phenomenon, triggered by developments in information technology and the changing needs of organisations. The concept combines in-office and remote working, offering flexibility that is expected to improve employee well-being and productivity. While there is a wealth of research on hybrid working models, there is a lack of understanding about the experiences of Human Resources (HR) in this context, particularly in relation to the impact on their behaviour and performance. This is important to study given the challenges and opportunities that arise in this transition. This research offers a new perspective by focusing on the direct experiences of employees in a hybrid working model, providing deep insights into how this approach affects their daily behaviour and performance. This research aims to explore and analyse HR experiences in hybrid working models and their impact on employee behaviour and performance across different industry sectors. This research uses a qualitative approach with in-depth interviews and focus group techniques. Data was collected from 30 participants from various industry backgrounds and analysed using thematic analysis techniques. Results show that hybrid working models provide significant benefits in improving work-life balance, but also present challenges in terms of communication and collaboration. Employees who adapted well to this model showed improvements in individual performance and job satisfaction. The findings of this study have important implications for HR management and organisational policy development.